2017
DOI: 10.1111/tog.12416
|View full text |Cite
|
Sign up to set email alerts
|

Contraceptive methods and issues around the menopause: an evidence update

Abstract: There have been a number of recent advances and an increase in the number of contraceptive methods available to perimenopausal women. Other relevant issues, including transition to and diagnosis of menopause, the use of hormone replacement therapy with contraception, and when to stop contraception, are discussed. Some hormonal contraceptives have added benefits in the management of common perimenopausal gynaecological problems. Research and development into intrauterine contraception, microchip drug release te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 38 publications
1
4
0
Order By: Relevance
“…The results in table (3) regarding the use of contraceptive methods; (53%) of women reporting that they were using contraceptive pills for duration of two years (54.5%), This result is consistent with the study obtained by Bakour et al, (2017) who found that Oral contraception is favored by many women. In women with comorbidities, progesterone-only pills (POPs) are an important alternative to CHC: the low progesterone dose has few contraindications, and POPs can be safely continued before normal fertility is lost (20) . Many women prefer to use the contraceptive pill because it is easy to use, inexpensive, and many women are unaware of the disadvantages of these pills when they are used it for the long time of their life.…”
Section: Table (3) Distribution Of Women According To Their Previous ...supporting
confidence: 88%
“…The results in table (3) regarding the use of contraceptive methods; (53%) of women reporting that they were using contraceptive pills for duration of two years (54.5%), This result is consistent with the study obtained by Bakour et al, (2017) who found that Oral contraception is favored by many women. In women with comorbidities, progesterone-only pills (POPs) are an important alternative to CHC: the low progesterone dose has few contraindications, and POPs can be safely continued before normal fertility is lost (20) . Many women prefer to use the contraceptive pill because it is easy to use, inexpensive, and many women are unaware of the disadvantages of these pills when they are used it for the long time of their life.…”
Section: Table (3) Distribution Of Women According To Their Previous ...supporting
confidence: 88%
“…In such circumstance, women of premenopausal stage preferred to exempt contraceptive, and consequently accounted for low contraceptive use. 33,34 The current study also identified three statistically significant factors to that influence contraceptive use. 35 First, the age of women was identified as one of the predictors for contraceptive use, where the tendency of utilization increases with age.…”
Section: Discussionmentioning
confidence: 67%
“…In such circumstance, women of premenopausal stage preferred to exempt contraceptive, and consequently accounted for low contraceptive use. 33 , 34 …”
Section: Discussionmentioning
confidence: 99%
“…45 Therefore, premenopausal women with chronic diseases and other comorbidities could use progestin implants as they are safer compared to DMPA until menopause. 44 This study reports a low (1.25%) utilization rate of combined oral contraception (COCs) among women aged 40-44 and more than 50 years while none of those aged 45-49 years used COCs. These ndings are consistent with ndings from other demographic health surveys conducted in Ethiopia 46 and Nigeria 47 where low rates of COC use of 2.1% and 1.4% respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, its high effectiveness, convenience, relatively long duration of action and secrecy especially in women whose spouses oppose the use of contraceptives could contribute to the high usage 43 . The low adoption of DMPA in countries with developed economies could be because progestin injectables, pills and implants have unwanted side effects such as heavy, irregular, prolonged uterine bleeding 44 . For late reproductive age women with a desire for conception, DMPA causes fertility delay which is ruinous when it co-exists with advanced maternal age.…”
Section: Resultsmentioning
confidence: 99%